Misrepresentations of Africa in contemporary Slovene school textbooks - Pirc, Janez (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2010)
Inspection of contemporary Slovene geography textbooks discloses continuing questionable images of Africa, such as 'the favourableness (of the African regions) for the settlement of the Whites' and a discourse of races and tribes. Misrepresentations of Africa of such a kind were to be expected in the late stage of European colonialism. The common denominator behind this is Eurocentrism, which has a strong influence on the occurrence of occasional racial views and the prevailing negative image of Africa. There is a lack of wider socio-political, historical and economic context as well as a great shortage of positive images - both written and visual - in the contents of the textbooks. These problems were identified in a detailed analysis of a selected number of geography textbooks for Slovene primary and secondary schools. The article presents the results of this analysis in a form of a categorization of common misrepresentations of Africa, and explains the basic institutional elements influencing the contents of the textbooks. The author offers examples of concrete solutions to the contents that are criticized here, explains what has already been done to balance the images of Africa, and states what actions should still be taken to attain its quality presentation in Slovene geography textbooks.
Keywords: Africa; Afrika; učbeniki; učbeniki za osnovne šole; učbeniki za srednje šole; geografija; geography; Slovenia; Slovenija